CLINICAL AND ECONOMIC EVALUATION OF CHRONIC DISEASE TREATMENT: A DISCREPANCY BETWEEN THE TRADITIONAL PHARMACOECONOMIC AND SOCIO-ECONOMIC ANALYSES - O. V. Zhukova (Фармакоэкономика, 2017)
The article presents the results of traditional pharmaco-economic analysis (the “cost-effectiveness” method) and socio-economic analysis of pharmaco-therapeutic regimens in a chronic disease.The specific aim was to compare the methods of pharmaco-economic and socioeconomic analyses when applied to the treatment of children with chronic asthma exacerbations.Materials and methods. The data on basic therapy of asthma exacerbations in children hospitalized in 2014-2015 were used (total 608 cases).Results. The combination of an inhaled glucocorticosteroid and long-acting β2-agonists proved to be the most optimal therapy as far as pharmaco-economics is concerned. The ways to calculate the coefficient of incremental costs of therapeutic regimens are shown. The discrepancy between the results of pharmacoeconomic analysis, on the one hand, and the data on socio-economic losses, on the other hand, was documented. The addition of montelukast (a leukotriene receptor antagonist) in the treatment regimen leads to an increase in medical costs from 873.00 rubles to 1515.39 rubles, and to a decrease in the average number of hospitalizations per year. In this case, the number of days of absence from work for a parent also decreases, which contributes to a higher GDP. As exemplified in this model group of 1000 patients, an increase in the direct medical costs by 734 thousand rubles leads to a decrease in the socio-economic losses (saving 34 million rubles.)Сonclusion. The traditional pharmacoeconomic analysis is the ideal instrument to compare between the original and generic drugs, and to evaluate the treatment of acute diseases. With respect to chronic diseases, this pharmaco-economic analysis should be used with caution. Without taking into account the effectiveness of the analyzed pharmacotherapy in treating possible exacerbations, or the transition to a more severe / mild form of the disease, the clinical component of the pharmaco-economic analysis may be missed. And if so, only the economic component of the selected therapy will play the major role in the final assessment. In this case, the results of the entire pharmaco-economic analysis may become less significant as they will reflect the least expensive treatment only, leaving behind the clinical aspects, e. g. the number of positive outcomes.